The Trend of the Nursing Research for Infertility: Focusing Psychological Aspects - MORI, Akiko; MURAMOTO, Junko (Journal of Japan Academy of Midwifery, 1992)
The purpose of this study was to clarify the characteristics of the nursing studies related to a psychological aspect of the patients with infertility, and to identify for needs of the further study. A systematic review of the literatures were conducted in order to analyze topics classification and its trends by years. The literatures related to the psychological aspects were selected and compared with their research questions, subjects, and methods. As a result, the number of the related literatures increased since 1980s, and of the literatures focusing on the patients experiences, meanings, and coping behavior increased remarkably since 1990s, however there was a few number of Japanese literatures generally within the way of reference used on this study. It was found that the focus of the studies were on what the patients had experiencd, and the couple or female patients with infertility were selected, and qualitative reserach methods were used. In conclusion, the studies were limited on couple or female, more study needed on male. Studies were limited superficially on phenomena, more study shall be encouraged to clarify the factors related to the phenomena.